Composting-vermicomposting of pigeon dropping waste. A contribution to the reduction of urban contamination - Carolina Elisabet Masin; Alejandra Duran; Cristina Susana Zalazar; Maria Emilia Fernandez (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: Without a proper treatment, pigeon dropping waste (PDW) in the urban environment is a sanitary risk for the population because of nasty and irritating odors, a very high content of ammonium, and the presence of pathogens. This study deals with the recycling of PDW from a dovecote, situated in a public city plaza, to achieve its stabilization and eliminate sanitary risks.